To, co dalekie, i to, co bliskie - nazwy własne i ich funkcje w materiałach do nauki języka angielskiego dla polskich emigrantów wojennych z czasów drugiej wojny światowej = What is distant and what is close - proper names and their functions in English learning materials for Polish war emigrants from the Second World War - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article aims to discuss the proper names used in the materials for learning English from 1941?1946 for the Poles living in war emigration and the functions that this resource performs. The study is not a comprehensive approach to the issue but rather an attempt to indicate the interpretative possibilities brought primarily by observing the context of "nomina propria" usage in publications documenting teaching English in a war situation.
Keywords: onimy; podręcznik glottodydaktyczny; dyskurs glottodydaktyczny; język angielski - nauczanie; proper names; language teaching book; language teaching discourse; English language